System-thinking progress in engineering programs: A case for broadening the roles of students - Tamir, Ram; Ben-Zvi Assaraf, Orit; Maman, Shimrit (Frontiers in Education, 2023)
Introduction Complex systems are prevalent in many scientific and engineering disciplines, which makes system thinking important for students of these fields. Duchifat 3 is a unique engineering educational extracurricular program, where high school students designed, assembled, and tested a nano-satellite. Methods This study applied qualitative methods to explore how the participants’ systems-thinking developed during the program. Participants were interviewed using the repertory grid interview, and a semi structured interview at the beginning and at the end of the project, while various observations were conducted throughout. Results While the participants were initially assigned narrow roles, each dealing with a single sub-system of the satellite, some chose to be involved with other sub-systems and aspects of the project. Our findings show that the broader the participants’ involvement was, the greater the progress they experienced in their systems-thinking. Participants who stayed focused on a single subsystem did not show progress, while participants who involved themselves with several sub-systems exhibited a more meaningful progress. Discussion Although the program design aimed to assign students to a narrow role to enable them to achieve the educational goals, from the perspective of systems-thinking this was counterproductive. These findings shed light on the design of engineering programs such as the one examined here in terms of systems-thinking development. We discuss the implications of the findings for similar programs and make suggestions for improvement.